Developing a framework for responsible downsizing through best fit: the importance of regulatory, procedural, communication and employment responsibilities - McLachlan, Christopher J. (Taylor and Francis, 2021)
The COVID-19 crisis has caused a wave of redundancies globally. This has brought the organisational practice of downsizing into sharp relief. Responsible downsizing is broadly understood as the actions, practices and strategies adopted by organisations to ameliorate the negative effects of redundancy. The paper draws on HR theories of best practice and best fit to explore the phenomenon of responsible downsizing, as a dominant focus in extant literature is the identification of ‘responsible’ best practices. In challenging these prevailing assumptions, this paper contends that responsible downsizing is more usefully understood as theoretically underpinned by a best fit approach. While there is value in adopting best practices the paper argues that greater attention should be paid to how organisational, societal and institutional contexts shape their implementation. Based on a review of 44 empirical articles, the paper advances a framework for responsible downsizing. The framework establishes four types of responsibility: regulatory, procedural, communication and employment responsibilities. Critical areas for future research are also mapped along with conceptual and practical implications.
Keywords: best fit; Downsizing; best practice; responsibility; HRM